Industrial noise: A new stimulus for dental pulp aging? Qualitative and quantitative analysis in Wistar rat teeth–A pilot study - Cavacas, Maria Alzira; Doroteia, Carolina; Leonardo, Ana Margarida; Proença, Luís; Tavares, Vítor (Frontiers in Oral Health, 2022)
Morphological changes induced by industrial noise have been experimentally observed in several organs. This study aims to characterize the effect of industrial noise on the pulp-dentin complex of Wistar rats from a histological point of view, through qualitative and quantitative analysis. The histologic cuts were observed over the optical microscope and photographed using 10x and 40x magnifications and measured with ImageJ software. They refer to animals exposed to industrial noise for 3 months and for 7 months and another group of animals kept in silence for control and sacrificed at the same time as the exposed groups. Concerning the qualitative observations, there was an apparent decrease in cell density in teeth of the animals exposed for 3 months compared to control teeth. However, in the group exposed for 7 months, there were no statistically significant differences. Even so, we found an evident correlation between exposure to industrial noise and its effects on the teeth. The morphological changes observed are similar to the modifications found on aged teeth. Therefore, this study places industrial noise as an aggressive stimulus that can cause a reaction of the pulp-dentin complex with morphological changes compatible with premature aging of the tooth.